Correspondence of James G. Douglas - Douglas, J. G. (James Green), 1887-1954; Green, Alice Stopford, 1848-1929 (1918)
Includes letters about the Irish Reconstruction Association from Horace Plunkett and Frank Cruise O'Brien; a letter from R. Hutchinson about conscription in Ireland; an invitation to dinner from N.W. Rowell, president of the Privy Council of Canada and a letter from Alice Stopford Green about the Irish Convention of 1917-18. Other correspondents include Thomas Johnson and Evelyn Sharp. Contains also minutes of a conference of Young Friends held at Carlingford about the political situation in Ireland and their desire for peace; letters from Thomas Sterling Berry, the Church of Ireland bishop of Killaloe and the Bishop of Meath to H.T. Bewley about an appeal for funds for the Irish White Cross.
Keywords: Ireland -- Politics and government -- 1910-1921